UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN MATEMATIKA MATERI ‘BANGUN DATAR’ MENGGUNAKAN PENDEKATAN STEM - Alfarisi, Hafis; Marta, Rusdial; Nurhaswinda, Nurhaswinda; Fadhilaturrahmi, Fadhilaturrahmi; Fauziddin, Fauziddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is the low critical thinking of mathematics students in grade 4. This study aims to improve the critical thinking skills of grade 4 students of SDN 002 Pasir Sialang. This research is a classroom action research (PTK), which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were all grade 4 students totaling 18 students. Data collection techniques in the form of interview techniques, observation, documentation and tests. While the data analysis technique used is a combination of qualitative data and quantitative data. Based on the results of research that has been carried out through 2 cycles, at meeting 1 of cycle I, there were 9 students who were complete with a percentage of 50% with an overall average of 69 and at meeting 2 it rose to 11 students with a percentage of 62% with an overall average of 77.83. Whereas in cycle II, meeting 1, there were 13 students who were complete with a percentage of 72% with an overall average of 80.05 and an increase at meeting 2 to 15 students with a percentage of 84% with an overall average of 84.55. Based on the results of this study, it shows that by applying the STEM approach, it can improve the critical thinking ability of mathematics class 4 students of SDN 002 Pasir Sialang.